A Jelly-Eating Hitchhiker in the Mediterranean: Molecular Identification of Brachyscelus rapacoides Stephensen 1925 (Amphipoda: Brachyscelidae) in Greece - Konstantinos Kalaentzis; Paraskevi Louizidou; Gerasimos Kondylatos; Elisavet Kaitetzidou; Lyndall Pereira da Conceicoa; Mara Lawniczak; Alex Makunin; Jack Monaghan; Paul Heath; Craig Corton; James Watts; Michelle Smith; et al. (Thalassas: An International Journal of Marine Sciences, 2026)
The hyperiid amphipod Brachyscelus rapacoides is a warm-water species associated with gelatinous zooplankton. In the Mediterranean it has been reported in association with Rhopilema nomadica in both Israel and Turkey. Here, we document the first record of B. rapacoides in Greek waters, representing the first confirmed record for Europe, based on both morphological examination and DNA barcoding of the mitochondrial COI gene. Specimens were collected from the umbrella of infested R. nomadica from two localities in the southeastern Aegean Sea. Diagnostic morphological characters, particularly the dentition of gnathopods 1–2 and male antennal morphology, agree with published redescriptions of the species. Phylogenetic analyses placed the studied specimens within B. rapacoides , clearly separated from congeners. This finding extends the known distribution of the species westwards in the Mediterranean and further supports its close ecological association with R. nomadica . The record highlights the role of gelatinous hosts in facilitating dispersal of symbiotic hyperiids and underscores the importance of integrating molecular tools and citizen science observations for early detection of overlooked pelagic associates.

Twenty-four-hour blood pressure and CSF biomarkers of Alzheimer’s disease and related dementias in a community cohort - Madeline Gibson; William T. O’Brien; Ella Rowsthorn; Katherine H. Franks; Lachlan Cribb; Marina Cavuoto; Beaudan Campbell-Brown; Ian Harding; Meng Law; Trevor T.-J. Chong; Stuart J. McDonald; Terence J. O’Brien; et al. (GeroScience, 2026)
Hypertension in midlife is associated with increased dementia risk, yet its relationship with early pathological changes of Alzheimer’s disease and related dementias (ADRD) remains unclear. Unlike office blood pressure (BP), 24-h ambulatory BP (ABPM) may better reflect cardiovascular risk, but associations between 24-h BP measures with ADRD biomarkers are unknown. This cross-sectional study examined associations between BP and cerebrospinal fluid biomarkers of ADRD in mid-to-late life. Dementia-free participants ( n = 77; mean age = 67 [SD, 6]; 39% women) from the community-based Brain and Cognitive Health (BACH) cohort underwent office and 24-h ABPM assessments to calculate mean BP, nocturnal dipping, blood pressure variability (BPV, coefficient of variation) across 24-h, awake and asleep periods. Participants also completed a lumbar puncture to assess ADRD biomarkers: Aβ42/Aβ40 ratio, phosphorylated tau at threonine 217 (pTau217), glial fibrillary acidic protein (GFAP), and neurofilament light chain (NfL). Linear regression models examined associations between BP and ADRD biomarkers, adjusting for age, sex, BMI, smoking, anti-hypertensive medication use, and APOE ε4 status. Higher 24-h and awake mean BP were associated with higher GFAP (24-h: per 1-SD unit increase, β = 1606.6 pg/mL, p = .03; awake: β = 1668.pg/mL, p = .03) and NfL (24-h: β = 172.3 pg/mL, p = .03; awake: β = 162.3 pg/mL, p = .04) levels. Elevated asleep BPV was associated with higher Aβ42/Aβ40 ratio ( β = 0.01, p = .01). No, other clear associations were identified for the other BP metrics ( p > .05 for all). Findings indicate that elevated BP is associated with neuronal injury and astrocytic reactivity, suggesting possible pathways through which BP may relate to neurodegenerative processes, independent of overt amyloid or tau.

Improving spine‐based age estimation in centrarchid fishes using otolith‐derived training sets - Matthew P. Woo; Stuart E. Jones; Brian S. Ankrapp; Avi Neumann; Julián Torres‐Dowdall (Journal of Fish Biology, 2026)
Nonlethal age determination is a priority in fish biology contexts where sacrifice is restricted, but estimates derived from nonlethally attainable structures tend to suffer from poor precision and accuracy relative to necessarily lethal, otolith‐derived estimates. Dorsal spines, while less accurate than otoliths, have shown higher precision compared to other alternative structures, making them a useful candidate for testing reader‐based approaches to improved age estimation. Here, we test whether small, lake‐specific training sets derived from paired otolith‐spine images, derived from incidental mortalities can provide useful calibration to spine‐based age estimates in four centrarchid populations from the northern Midwest, including two largemouth bass ( Micropterus nigricans ) and two bluegill ( Lepomis macrochirus ) populations. Five moderately experienced readers estimated ages from spine images before and after calibration with paired otolith‐spine images. Calibration consistently resulted in increased estimated ages, particularly for older fish, and reduced variability among readers in both individual age estimates and predicted length‐at‐age trajectories. Specifically, we find that these structured training sets are useful in both reducing traditional underestimation biases and reducing reader‐based variance effects at both the level of individual estimates and in growth modelling contexts. Therefore, they may offer a practical means of leveraging available incidental mortalities in the improvement of otherwise nonlethal aging programs. Accordingly, we suggest that where available, readers first be familiarized with lake‐specific paired otolith‐spine images before independently estimating spine ages.

Effects of duration of a plant-based diet stimulus at first feeding on nutritional programming in Atlantic salmon (Salmo salar) - Xu Gong; Matthew Sprague; Stuart McMillan; Pedro Gómez-Requeni; Fernando Norambuena; Sam A. M. Martin; Douglas R. Tocher; Mónica B. Betancor (Fish Physiology and Biochemistry, 2026)
Nutritional programming could potentially be a strategy for sustainable aquaculture to adapt fish to feeds formulated with low levels of marine ingredients. The present study examined the effects of early dietary stimulus duration and the impacts of a later challenge with a similar diet. At first feeding, Atlantic salmon ( Salmo salar ) fry of ~ 0.15 g initial weight were fed a vegetable diet (77% plant-based ingredients) for either 1 (V1) or 2 weeks (V2), while a control group (M) received a marine diet (86% marine-based ingredients) for the 2 weeks (stimulus phase). All fish then received a marine diet for 16 weeks (intermediate phase) before being refed a vegetable diet for 6 weeks (challenge phase). Water temperature was 13 °C during the trial, and the only difference between the three experimental groups (V1, V2 and M) was their dietary regime during the first 2 weeks. Obviously, stimulus duration had no phenotypic impacts on growth or tissue fatty acid compositions of either total or polar lipids after challenge. However, the expressions of key genes of LC-PUFA biosynthesis were upregulated significantly in the V1 group, whereas the expressions of most transcription factors were downregulated in the V2 group. After the challenge, the circular muscle thickness of the intestine in the V1 group was increased by 15%, and goblet cell numbers were reduced by 15%. Overall, further investigations about the duration of the stimulus and assessment with longer challenges are required to elicit positive effects and to refine the use of nutritional programming in Atlantic salmon.

Addressing how spatial resolution affects image velocimetry outputs: implications for measurements from space - Harley Dixey; Edward Rollason; Stuart Dunning; Matthew Thomas Perks (Hydrological Sciences Journal, 2026)

Morrittospora corbiculae n. gen. n. sp., a microsporidian parasite infecting the invasive Asian clam Corbicula fluminea from the River Thames, London - Rachel Foster; Kelly S. Bateman; Paul F. Clark; Matthew J. Green; Chantelle Hooper; Stuart H. Ross; Paul Stebbing; Georgia M. Ward; David Bass (Journal of Invertebrate Pathology, 2026)

deadtrees.earth — An open-access and interactive database for centimeter-scale aerial imagery to uncover global tree mortality dynamics - Clemens Mosig; Janusch Vajna-Jehle; Miguel D. Mahecha; Yan Cheng; Henrik Hartmann; David Montero; Samuli Junttila; Stéphanie Horion; Mirela Beloiu Schwenke; Michael J. Koontz; Khairul Nizam Abdul Maulud; Stephen Adu-Bredu; et al. (Remote Sensing of Environment, 2026)

Factor analysis of multimodal MRI, biofluid, and vascular biomarkers reveals latent constructs of brain health - Ella Rowsthorn; Ming Ann Sim; William T. O’Brien; Stuart J. McDonald; Katherine Franks; Benjamin Sinclair; Trevor T.-J. Chong; Stephanie Yiallourou; Marina Cavuoto; Lucy Vivash; Terence J. O’Brien; Xingfeng Shao; et al. (GeroScience, 2025)
Individual imaging and fluid biomarkers provide insights into specific components of brain health, but integrated multimodal approaches are necessary to capture the complex, interrelated biological systems that contribute to brain homeostasis and neurodegenerative disease. Using data from the Brain and Cognitive Health (BACH) cohort study ( N = 127; mean age = 67 years, 68% women), we performed an exploratory factor analysis to identify latent constructs of brain health. We included multimodal neurovascular imaging markers, brain atrophy metrics, plasma Alzheimer’s disease (AD) biomarkers, and cardiovascular risk factors. Five constructs emerged: “Brain & Vascular Health” (greater hippocampal volume, basal ganglia enlarged perivascular spaces (ePVS), cerebral blood flow, and HDL cholesterol; lower ventricle volume and BMI), “Structural Integrity” (greater cortical thickness, fractional anisotropy, and basal ganglia ePVS), “White Matter (WM) Fluid Dysregulation” (greater WM ePVS and Free Water), “AD Biomarkers” (higher phosphorylated tau [pTau]181 and pTau217; lower amyloid-beta 42/40 ratio), and “Neuronal Injury” (higher glial fibrillary acidic protein and neurofilament light chain). All constructs were associated with age (β = - 0.70–0.39, p ≤ 0.014), except for WM Fluid Dysregulation ( p > 0.05). Brain and Vascular Health and Structural Integrity (partial r = 0.305, p < 0.001) and AD biomarkers and neuronal injury (partial r = 0.248, p = 0.005) were positively correlated. Only Brain and Vascular Health was associated with global cognition (β = 0.27, SE = 0.13, p = 0.043). These findings provide a data-driven framework for examining distinct constructs underlying vascular health, fluid regulation, and neurodegenerative pathology. We demonstrate the utility of using multiple biomarkers to probe these biological systems, paving the way for future research to explore how these systems change across diverse neurodegenerative conditions. Graphical abstract

Wildfire smoke and PM2.5 pollution in Chicago: Evidence from 2019 to 2023 - Nora Hartnett; Ping Jing; Bo Zhang; Matthew Stuart; Jun Wang (Urban Climate, 2025)

A provably stable numerical method for the anisotropic diffusion equation in confined magnetic fields - Dean Muir; Kenneth Duru; Matthew Hole; Stuart Hudson (Computer Physics Communications, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Soil Carbon Saturation: What Do We Really Know? - Katerina Georgiou; Denis Angers; Ryan E. Champiny; M. Francesca Cotrufo; Matthew E. Craig; Sebastian Doetterl; A. Stuart Grandy; Jocelyn M. Lavallee; Yang Lin; Emanuele Lugato; Christopher Poeplau; Katherine S. Rocci; et al. (Global Change Biology, 2025)
Managing soils to increase organic carbon storage presents a potential opportunity to mitigate and adapt to global change challenges, while providing numerous co‐benefits and ecosystem services. However, soils differ widely in their potential for carbon sequestration, and knowledge of biophysical limits to carbon accumulation may aid in informing priority regions. Consequently, there is great interest in assessing whether soils exhibit a maximum capacity for storing organic carbon, particularly within organo–mineral associations given the finite nature of reactive minerals in a soil. While the concept of soil carbon saturation has existed for over 25 years, recent studies have argued for and against its importance. Here, we summarize the conceptual understanding of soil carbon saturation at both micro‐ and macro‐scales, define key terminology, and address common concerns and misconceptions. We review methods used to quantify soil carbon saturation, highlighting the theory and potential caveats of each approach. Critically, we explore the utility of the principles of soil carbon saturation for informing carbon accumulation, vulnerability to loss, and representations in process‐based models. We highlight key knowledge gaps and propose next steps for furthering our mechanistic understanding of soil carbon saturation and its implications for soil management.

Estimating the trapping area and density of common whelk (Buccinum undatum) using experimental fishing - Matthew J. Garratt; Isobel S.M. Bloor; Matthew T. Coleman; Charlotte N. Colvin; Jan Geert Hiddink; Natalie Hold; Stuart R. Jenkins (Fisheries Research, 2025)

Dispelling myths: Reviewing the evidence on zoning reforms in Auckland - Stuart Donovan; Matthew Maltman (Land Use Policy, 2025)

More than the sum of their parts — Environmental flows increase fish movement and fishway functionality - Matthew Jones; Paul Moloney; Robin Hale; Ivor Stuart; Justin O'Connor; Zeb Tonkin (Ecological Engineering, 2025)

Redefining the role of sodium exclusion within salt tolerance - Sebastian Garcia-Daga; Stuart J. Roy; Matthew Gilliham (Trends in Plant Science, 2025)

Fish and invertebrate communities show greater day–night partitioning on tropical than temperate reefs - Tyson R. Jones; Graham J. Edgar; Rowan Trebilco; Camille Mellin; Rick D. Stuart‐Smith; Lara Denis‐Roy; Olivia J. Johnson; Matthew Rose; Scott D. Ling (Ecology, 2025)
Diel partitioning of animals within ecological communities is widely acknowledged, yet rarely quantified. Investigation of most ecological patterns and processes involves convenient daylight sampling, with little consideration of the contributions of nocturnal taxa, particularly in marine environments. Here we assess diel partitioning of reef faunal assemblages at a continental scale utilizing paired day and night visual census across 54 shallow tropical and temperate reefs around Australia. Day–night differences were most pronounced in the tropics, with fishes and invertebrates displaying distinct and opposing diel occupancy on coral reefs. Tropical reefs in daytime were occupied primarily by fishes not observed at night (64% of all species sighted across day and night, and 71% of all individuals). By night, substantial emergence of invertebrates not otherwise detected during sunlit hours occurred (56% of all species, and 45% of individuals). Nocturnal emergence of tropical invertebrates corresponded with significant declines in the richness and biomass of predatory and herbivorous diurnal fishes. In contrast, relatively small diel changes in fishes active on temperate reefs corresponded to limited nocturnal emergence of temperate invertebrates. This reduced partitioning may, at least in part, be a result of strong top‐down pressures from fishes on invertebrate communities, either by predation or competitive interference. For shallow reefs, the diel cycle triggers distinct emergence and retreat of faunal assemblages and associated trophic patterns and processes, which otherwise go unnoticed during hours of regular scientific monitoring. Improved understanding of reef ecology, and management of reef ecosystems, requires greater consideration of nocturnal interactions. Without explicit sampling of nocturnal patterns and processes, we may be missing up to half of the story when assessing ecological interactions.

The diversity, frequency and severity of natural hazard impacts on subsea telecommunications networks - Lucy Bricheno; Isobel Yeo; Michael Clare; James Hunt; Allan Griffiths; Lionel Carter; Peter J. Talling; Megan Baker; Stuart Wilson; Matthew West; Semisi Panuve; Samuiela Fonua (Earth-Science Reviews, 2024)

Establishing the role of the North Atlantic Oscillation as a potential driver of brown crab Cancer pagurus density - Matthew T. Coleman; Isobel S.M. Bloor; Stuart R. Jenkins (Fisheries Research, 2024)

Remote sensing of artisanal and small-scale mining: A review of scalable mapping approaches - Ilyas Nursamsi; Stuart R. Phinn; Noam Levin; Matthew Scott Luskin; Laura Jane Sonter (Science of The Total Environment, 2024)

Large-scale serial replacement of invasive tench (Tinca tinca) by invasive carp (Cyprinus carpio) in the presence of redfin perch (Perca fluviatilis) in the Murray-Darling River system, Australia - Matthew P. Hill; Peter Caley; Ivor Stuart; Richard P. Duncan; David M. Forsyth (Biological Invasions, 2024)
Ecosystems worldwide are increasingly being invaded by multiple species, and the rate of biological invasion is accelerating, leading to more interactions among invasive species. One such interaction that has received little attention is the phenomenon of ‘serial replacement’ or ‘over-invasion’, where an established invasive species is supplanted by a second invasive species. Understanding this interaction is important as controlling the second species could inadvertently lead to an increase in the abundance of the first species. We used a hierarchical state-space model to analyse changes in annual abundances (commercial catch-per-unit-effort) of three invasive fish species, tench ( Tinca tinca ), common carp ( Cyprinus carpio ) and redfin perch ( Perca fluviatilis ), in the Murray-Darling River system (MDRS), Australia between 1954–2002. Tench were present at low abundances until the mid-1970 s, before declining to the point of no commercial catch post-1989. This rapid decline coincided with a significant increase in carp abundance, suggesting that carp may have driven the tench decline through habitat modification (particularly the destruction of aquatic plants), consistent with findings from European studies that show the disappearance of tench from ponds with intensive carp farming. Redfin perch populations, were inferred to be much less impacted by the invading carp population. While carp were present in the MDRS for the duration of the study, the rapid increase in carp abundance in the early 1970 s coincided with the introduction of a specific genetic lineage—the “Boolarra strain”. Our analysis provides compelling evidence of serial replacement of long-established tench by invading common carp triggered by the introduction of a novel carp strain.

Biotransformation of 6:2/4:2 fluorotelomer alcohols by Dietzia aurantiaca J3: Enzymes and proteomics - Shefali Bhardwaj; Matthew Lee; Denis O'Carroll; James McDonald; Keith Osborne; Stuart Khan; Russell Pickford; Nicholas Coleman; Casey O’Farrell; Sarah Richards; Michael J. Manefield (Journal of Hazardous Materials, 2024)

Rock fishways: Natural designs for an engineered world - Ivor G. Stuart; Timothy J. Marsden; Matthew J. Jones; Matt T. Moore; Lee J. Baumgartner (Ecological Engineering, 2024)

Limited spatial co-occurrence of wildfire and prescribed burning on moorlands in Scotland - Debbie Fielding; Scott Newey; Robin J. Pakeman; Dave Miller; Zisis Gagkas; Keith Matthews; Stuart W. Smith (Biological Conservation, 2024)

Bottom simulating reflections across the northern Gulf of Mexico slope - Aditya Kumar; Ann E. Cook; Alexey Portnov; Stuart Skopec; Matthew Frye; Stephen Palmes (Marine and Petroleum Geology, 2024)

Overcome imposter syndrome: Contribute to working groups and build strong networks - Amanda E. Bates; Megan A. Davies; Rick D. Stuart-Smith; Natali Lazzari; Jonathan S. Lefcheck; Scott D. Ling; Camille Mellin; David Mouillot; Anthony T.F. Bernard; Scott Bennett; Christopher J. Brown; Michael T. Burrows; et al. (Biological Conservation, 2024)

Conservation genomics of the threatened Trispot Darter (Etheostoma trisella) - Kayla M. Fast; Brook L. Fluker; Bernard R. Kuhajda; Patrick E. O’Neil; Stuart W. McGregor; Matthew S. Piteo; Michael W. Sandel (Conservation Genetics, 2024)

On the sensitivity of fire-weather climate projections to empirical fire models - Kevin J. Tory; Miguel G. Cruz; Stuart Matthews; Musa Kilinc; W. Lachlan McCaw (Agricultural and Forest Meteorology, 2024)

Quality and risk management frameworks for biosolids: An assessment of current international practice - Marilyn F. Braine; Matthew Kearnes; Stuart J. Khan (Science of The Total Environment, 2024)

Rarity mediates species‐specific responses of tropical reef fishes to protection - Loïc Sanchez; Nicolas Loiseau; Graham J. Edgar; Cyril Hautecoeur; Fabien Leprieur; Stéphanie Manel; Matthew McLean; Rick D. Stuart‐Smith; Laure Velez; David Mouillot (Ecology Letters, 2024)
Marine protected areas (MPAs) are the most widely applied tool for marine biodiversity conservation, yet many gaps remain in our understanding of their species‐specific effects, partly because the socio‐environmental context and spatial autocorrelation may blur and bias perceived conservation outcomes. Based on a large data set of nearly 3000 marine fish surveys spanning all tropical regions of the world, we build spatially explicit models for 658 fish species to estimate species‐specific responses to protection while controlling for the environmental, habitat and socio‐economic contexts experienced across their geographic ranges. We show that the species responses are highly variable, with ~40% of fishes not benefitting from protection. When investigating how traits influence species' responses, we find that rare top‐predators and small herbivores benefit the most from MPAs while mid‐trophic level species benefit to a lesser extent, and rare large herbivores experience adverse effects, indicating potential trophic cascades.

Relationship between attentional bias and stimulus control: An observational study of real-world eating patterns - Stefania Franja; Katherine G. Elliston; Anna E. McCrae; Allison J. Matthews; Stuart G. Ferguson (Appetite, 2023)

Distribution transforms for guiding center orbit coordinates in axisymmetric tokamak equilibria - Stuart Benjamin; Henrik Järleblad; Mirko Salewski; Luke Stagner; Matthew Hole; David Pfefferlé (Computer Physics Communications, 2023)

Effective rhizobia enhance legume growth during subsequent drought despite water costs associated with nitrogen fixation - Stuart T. Schwab; Kenjiro W. Quides; Camille E. Wendlandt; Jerry Trinh; Matthew Sung; Paola Cardenas; Michael Torres; Louis S. Santiago; Loralee Larios; Joel L. Sachs (Plant and Soil, 2023)

Assessing Pleistocene–Holocene climatic and environmental change in insular Near Oceania using stable isotope analysis of archaeological fauna - Patrick Roberts; Sean Hixon; Rebecca Hamilton; Mary Lucas; Jana Ilgner; Sara Marzo; Stuart Hawkins; Sindy Luu; Chris Gosden; Matthew Spriggs; Glenn Summerhayes (Journal of Quaternary Science, 2023)
In comparison to temperate and arid regions, environmental responses to the Last Glacial Maximum and the Terminal Pleistocene and Holocene boundary remain poorly known for many parts of the tropics, making it challenging to unravel human–landscape interactions across this timeframe. This is particularly the case in insular Near Oceania, where sea‐level fluctuations and potential changes in forest cover may have had major impacts on hunter–gatherer populations. Here, we apply stable carbon and oxygen isotope analyses to small‐mammal teeth from four Pleistocene–Holocene (spanning from 29 000 years ago to the late Holocene) sequences in the Bismarck Archipelago to reconstruct changes in environments directly exploited by human populations in this part of the world. Our results show a subtle response of tropical habitats in Near Oceania to relatively arid conditions during the late‐glacial period, something that has also been observed at sites in South and Southeast Asia, followed by a Terminal Pleistocene–Holocene expansion of tropical forest cover. Nevertheless, site‐based variability in environmental responses across this period highlight the need for more multidisciplinary studies of human occupation sequences in a region that is becoming increasingly central to exploring human adaptations, environmental modifications and social network development over the past 20 000 years.

Droplet-based millifluidic synthesis of a proton-conducting sulfonate metal–organic framework - Chao Sun; Matthew Barton; Christopher M. Pask; Mohamed Edokali; Lina Yang; Andrew J. Britton; Stuart Micklethwaite; Francesco Iacoviello; Ali Hassanpour; Maximilian Besenhard; Rik Drummond-Brydson; Ke-Jun Wu; et al. (Chemical Engineering Journal, 2023)

Understanding the effect of metamictization on the efficiency of zircon milling - Matthew J. Smith; Emma Jones; Stuart Blackburn; Richard W. Greenwood (Minerals Engineering, 2023)

Frontiers of Mathematical Biology: A workshop honouring Professor Edmund Crampin - Robyn Araujo; Douglas Brumley; Joe Cursons; Karen Day; Matthew Faria; Jennifer A. Flegg; Domenic Germano; Hilary Hunt; Peter Hunter; Adrianne Jenner; Stuart Johnston; James M. McCaw; et al. (Mathematical Biosciences, 2023)

Extensive regional variation in the phenology of insects and their response to temperature across N orth A merica - Peter O. Dunn; Insiyaa Ahmed; Elise Armstrong; Natasha Barlow; Malcolm A. Barnard; Marc Bélisle; Thomas J. Benson; Lisha L. Berzins; Chloe K. Boynton; T. Anders Brown; Melissa Cady; Kyle Cameron; et al. (Ecology, 2023)
Climate change models often assume similar responses to temperatures across the range of a species, but local adaptation or phenotypic plasticity can lead plants and animals to respond differently to temperature in different parts of their range. To date, there have been few tests of this assumption at the scale of continents, so it is unclear if this is a large‐scale problem. Here, we examined the assumption that insect taxa show similar responses to temperature at 96 sites in grassy habitats across North America. We sampled insects with Malaise traps during 2019–2021 ( N = 1041 samples) and examined the biomass of insects in relation to temperature and time of season. Our samples mostly contained Diptera (33%), Lepidoptera (19%), Hymenoptera (18%), and Coleoptera (10%). We found strong regional differences in the phenology of insects and their response to temperature, even within the same taxonomic group, habitat type, and time of season. For example, the biomass of nematoceran flies increased across the season in the central part of the continent, but it only showed a small increase in the Northeast and a seasonal decline in the Southeast and West. At a smaller scale, insect biomass at different traps operating on the same days was correlated up to ~75 km apart. Large‐scale geographic and phenological variation in insect biomass and abundance has not been studied well, and it is a major source of controversy in previous analyses of insect declines that have aggregated studies from different locations and time periods. Our study illustrates that large‐scale predictions about changes in insect populations, and their causes, will need to incorporate regional and taxonomic differences in the response to temperature.

Funding evidence‐based conservation - Danni Parks; Nida Al‐Fulaij; Clare Brook; Stuart H. M. Butchart; Jean‐Gaël Collomb; David Cope; Simon Dowell; Becky Falkingham; Winifred F. Frick; Douglas Gibbs; Emily E. Gray; Nicolas Heard; et al. (Conservation Biology, 2022)

Fire‐related threats and transformational change in Australian ecosystems - David A. Keith; Stuart P. Allen; Rachael V. Gallagher; Berin D. E. Mackenzie; Tony D. Auld; Sarah Barrett; Anne Buchan; Valerie English; Carl Gosper; Dave Kelly; Allen McIllwee; Rachel T. Melrose; et al. (Global Ecology and Biogeography, 2022)
Aim Megafire events generate immediate concern for wildlife and human well‐being, but their broader ecological impacts likely extend beyond individual species and single fire events. In the first mechanistic study of fire effects focussed on ecosystems, we aimed to assess the sensitivity and exposure of ecosystems to multiple fire‐related threats, placing impacts in the context of changing fire regimes and their interactions with other threats. Location Southern and eastern Australia. Time period 2019–2020. Major species studied Australian ecosystems. Methods We defined 15 fire‐related threats to ecosystems based on mechanisms associated with: (a) direct effects of fire regime components; (b) interactions between fire and physical environmental processes; (c) effects of fire on biological interactions; and (d) interactions between fire and human activity. We estimated the sensitivity and exposure of a sample of 92 ecosystem types to each threat type based on published relationships and spatial analysis of the 2019–2020 fires. Results Twenty‐nine ecosystem types assessed had more than half of their distribution exposed to one or more threat types, and only three of those were listed as nationally threatened. Three fire‐related threat types posed the most severe threats to large numbers of ecosystem types: high frequency fire; pre‐fire drought; and post‐fire invasive predator activity. The ecosystem types most affected ranged from rain forests to peatlands, and included some, such as sclerophyllous eucalypt forests and heathlands, that are traditionally regarded as fire‐prone and fire‐adapted. Main conclusions Most impacts of the 2019–2020 fires on ecosystems became apparent only when they were placed in the context of the whole fire regime and its interactions with other threatening processes, and were not direct consequences of the megafire event itself. Our mechanistic approach enables ecosystem‐specific management responses for the most threatened ecosystem types to be targeted at underlying causes of degradation and decline.

Chemistry Manufacturing and Controls Development, Industry Reflections on Manufacture, and Supply of Pandemic Therapies and Vaccines - Matthew E. Popkin; Markus Goese; Diane Wilkinson; Stuart Finnie; Talia Flanagan; Cristiana Campa; Alexandra Clinch; Andrew Teasdale; Andrew Lennard; Graham Cook; Ganapathy Mohan; Matthew D. Osborne (The AAPS Journal, 2022)

Giant Tree Frog diversification in West and Central Africa: Isolation by physical barriers, climate, and reproductive traits - Kyle E. Jaynes; Edward A. Myers; Václav Gvoždík; David C. Blackburn; Daniel M. Portik; Eli Greenbaum; Gregory F. M. Jongsma; Mark‐Oliver Rödel; Gabriel Badjedjea; Abraham Bamba‐Kaya; Ninda L. Baptista; Jeannot B. Akuboy; et al. (Molecular Ecology, 2022)
Secondary sympatry amongst sister lineages is strongly associated with genetic and ecological divergence. This pattern suggests that for closely related species to coexist in secondary sympatry, they must accumulate differences in traits that mediate ecological and/or reproductive isolation. Here, we characterized inter‐ and intraspecific divergence in three giant tree frog species whose distributions stretch across West and Central Africa. Using genome‐wide single‐nucleotide polymorphism data, we demonstrated that species‐level divergence coincides temporally and geographically with a period of large‐scale forest fragmentation during the late Pliocene. Our environmental niche models further supported a dynamic history of climatic suitability and stability, and indicated that all three species occupy distinct environmental niches. We found modest morphological differentiation amongst the species with significant divergence in tympanum diameter and male advertisement call. In addition, we confirmed that two species occur in secondary sympatry in Central Africa but found no evidence of hybridization. These patterns support the hypothesis that cycles of genetic exchange and isolation across West and Central Africa have contributed to globally significant biodiversity. Furthermore, divergence in both ecology and reproductive traits appear to have played important roles in maintaining distinct lineages. At the intraspecific level, we found that climatic refugia, precipitation gradients, marine incursions, and potentially riverine barriers generated phylogeographic structure throughout the Pleistocene and into the Holocene. Further studies examining phenotypic divergence and secondary contact amongst these geographically structured populations may demonstrate how smaller scale and more recent biogeographic barriers contribute to regional diversification.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Global maps of soil temperature - Jonas J. Lembrechts; Johan van den Hoogen; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Julia Kemppinen; Martin Kopecký; Miska Luoto; Ilya M. D. Maclean; Thomas W. Crowther; Joseph J. Bailey; Stef Haesen; et al. (Global Change Biology, 2022)
Research in global change ecology relies heavily on global climatic grids derived from estimates of air temperature in open areas at around 2 m above the ground. These climatic grids do not reflect conditions below vegetation canopies and near the ground surface, where critical ecosystem functions occur and most terrestrial species reside. Here, we provide global maps of soil temperature and bioclimatic variables at a 1‐km 2 resolution for 0–5 and 5–15 cm soil depth. These maps were created by calculating the difference (i.e. offset) between in situ soil temperature measurements, based on time series from over 1200 1‐km 2 pixels (summarized from 8519 unique temperature sensors) across all the world's major terrestrial biomes, and coarse‐grained air temperature estimates from ERA5‐Land (an atmospheric reanalysis by the European Centre for Medium‐Range Weather Forecasts). We show that mean annual soil temperature differs markedly from the corresponding gridded air temperature, by up to 10°C (mean = 3.0 ± 2.1°C), with substantial variation across biomes and seasons. Over the year, soils in cold and/or dry biomes are substantially warmer (+3.6 ± 2.3°C) than gridded air temperature, whereas soils in warm and humid environments are on average slightly cooler (−0.7 ± 2.3°C). The observed substantial and biome‐specific offsets emphasize that the projected impacts of climate and climate change on near‐surface biodiversity and ecosystem functioning are inaccurately assessed when air rather than soil temperature is used, especially in cold environments. The global soil‐related bioclimatic variables provided here are an important step forward for any application in ecology and related disciplines. Nevertheless, we highlight the need to fill remaining geographic gaps by collecting more in situ measurements of microclimate conditions to further enhance the spatiotemporal resolution of global soil temperature products for ecological applications.

Persistent thermally driven shift in the functional trait structure of herbivorous fishes: Evidence of top‐down control on the rebound potential of temperate seaweed forests? - Nestor E. Bosch; Matthew McLean; Salvador Zarco‐Perello; Scott Bennett; Rick D. Stuart‐Smith; Adriana Vergés; Albert Pessarrodona; Fernando Tuya; Tim Langlois; Claude Spencer; Sahira Bell; Benjamin J. Saunders; et al. (Global Change Biology, 2022)
Extreme climatic events can reshape the functional structure of ecological communities, potentially altering ecological interactions and ecosystem functioning. While these shifts have been widely documented, evidence of their persistence and potential flow‐on effects on ecosystem structure following relaxation of extreme events remains limited. Here, we investigate changes in the functional trait structure – encompassing dimensions of resource use, thermal affinity, and body size – of herbivorous fishes in a temperate reef system that experienced an extreme marine heatwave (MHW) and subsequent return to cool conditions. We quantify how changes in the trait structure modified the nature and intensity of herbivory‐related functions (macroalgae, turf, and sediment removal), and explored the potential flow‐on effects on the recovery dynamics of macroalgal foundation species. The trait structure of the herbivorous fish assemblage shifted as a result of the MHW, from dominance of cool‐water browsing species to increased evenness in the distribution of abundance among temperate and tropical guilds supporting novel herbivory roles (i.e. scraping, cropping, and sediment sucking). Despite the abundance of tropical herbivorous fishes and intensity of herbivory‐related functions declined following a period of cooling after the MHW, the underlying trait structure displayed limited recovery. Concomitantly, algal assemblages displayed a lack of recovery of the formerly dominant foundational species, the kelp Ecklonia radiata , transitioning to an alternative state dominated by turf and Sargassum spp. Our study demonstrates a legacy effect of an extreme MHW and exemplified the value of monitoring phenotypic (trait mediated) changes in the nature of core ecosystem processes to predict and adapt to the future configurations of changing reef ecosystems.

Historical museum samples enable the examination of divergent and parallel evolution during invasion - Katarina C. Stuart; William B. Sherwin; Jeremy J. Austin; Melissa Bateson; Marcel Eens; Matthew C. Brandley; Lee A. Rollins (Molecular Ecology, 2022)
During the Anthropocene, Earth has experienced unprecedented habitat loss, native species decline and global climate change. Concurrently, greater globalization is facilitating species movement, increasing the likelihood of alien species establishment and propagation. There is a great need to understand what influences a species’ ability to persist or perish within a new or changing environment. Examining genes that may be associated with a species’ invasion success or persistence informs invasive species management, assists with native species preservation and sheds light on important evolutionary mechanisms that occur in novel environments. This approach can be aided by coupling spatial and temporal investigations of evolutionary processes. Here we use the common starling, Sturnus vulgaris , to identify parallel and divergent evolutionary change between contemporary native and invasive range samples and their common ancestral population. To do this, we use reduced‐representation sequencing of native samples collected recently in northwestern Europe and invasive samples from Australia, together with museum specimens sampled in the UK during the mid‐19th century. We found evidence of parallel selection on both continents, possibly resulting from common global selective forces such as exposure to pollutants. We also identified divergent selection in these populations, which might be related to adaptive changes in response to the novel environment encountered in the introduced Australian range. Interestingly, signatures of selection are equally as common within both invasive and native range contemporary samples. Our results demonstrate the value of including historical samples in genetic studies of invasion and highlight the ongoing and occasionally parallel role of adaptation in both native and invasive ranges.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Street-level green spaces support a key urban population of the threatened Hispaniolan parakeet Psittacara chloropterus - Matthew Geary; Celia J. Brailsford; Laura I. Hough; Fraser Baker; Simon Guerrero; Yolanda M. Leon; Nigel J. Collar; Stuart J. Marsden (Urban Ecosystems, 2021)
While urbanisation remains a major threat to biodiversity, urban areas can sometimes play an important role in protecting threatened species, especially exploited taxa such as parrots. The Hispaniolan Parakeet Psittacara chloropterus has been extirpated across much of Hispaniola, including from most protected areas, yet Santo Domingo (capital city of the Dominican Republic) has recently been found to support the island’s densest remaining population. In 2019, we used repeated transects and point-counts across 60 1 km 2 squares of Santo Domingo to examine the distribution of parakeets, identify factors that might drive local presence and abundance, and investigate breeding ecology. Occupancy models indicate that parakeet presence was positively related to tree species richness across the city. N-Mixture models show parakeet encounter rates were correlated positively with species richness of trees and number of discrete ‘green’ patches (> 100 m 2 ) within the survey squares. Hispaniolan Woodpecker Melanerpes striatus , the main tree-cavity-producing species on Hispaniola, occurs throughout the city, but few parakeet nests are known to involve the secondary use of its or other cavities in trees/palms. Most parakeet breeding (perhaps 50–100 pairs) appears to occur at two colonies in old buildings, and possibly only a small proportion of the city’s 1500+ parakeets that occupy a single roost in street trees breed in any year. Our models emphasise the importance of parks and gardens in providing feeding resources for this IUCN Vulnerable species. Hispaniola’s urban centres may be strongholds for populations of parakeets and may even represent sources for birds to recolonise formerly occupied areas on the island.

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

Testing a global standard for quantifying species recovery and assessing conservation impact - Molly K. Grace; H. Resit Akçakaya; Elizabeth L. Bennett; Thomas M. Brooks; Anna Heath; Simon Hedges; Craig Hilton‐Taylor; Michael Hoffmann; Axel Hochkirch; Richard Jenkins; David A. Keith; Barney Long; et al. (Conservation Biology, 2021)
Recognizing the imperative to evaluate species recovery and conservation impact, in 2012 the International Union for Conservation of Nature (IUCN) called for development of a “Green List of Species” (now the IUCN Green Status of Species). A draft Green Status framework for assessing species’ progress toward recovery, published in 2018, proposed 2 separate but interlinked components: a standardized method (i.e., measurement against benchmarks of species’ viability, functionality, and preimpact distribution) to determine current species recovery status (herein species recovery score ) and application of that method to estimate past and potential future impacts of conservation based on 4 metrics ( conservation legacy, conservation dependence , conservation gain , and recovery potential ). We tested the framework with 181 species representing diverse taxa, life histories, biomes, and IUCN Red List categories (extinction risk). Based on the observed distribution of species’ recovery scores, we propose the following species recovery categories : fully recovered, slightly depleted, moderately depleted, largely depleted, critically depleted, extinct in the wild, and indeterminate. Fifty‐nine percent of tested species were considered largely or critically depleted. Although there was a negative relationship between extinction risk and species recovery score, variation was considerable. Some species in lower risk categories were assessed as farther from recovery than those at higher risk. This emphasizes that species recovery is conceptually different from extinction risk and reinforces the utility of the IUCN Green Status of Species to more fully understand species conservation status. Although extinction risk did not predict conservation legacy, conservation dependence, or conservation gain, it was positively correlated with recovery potential. Only 1.7% of tested species were categorized as zero across all 4 of these conservation impact metrics , indicating that conservation has, or will, play a role in improving or maintaining species status for the vast majority of these species. Based on our results, we devised an updated assessment framework that introduces the option of using a dynamic baseline to assess future impacts of conservation over the short term to avoid misleading results which were generated in a small number of cases, and redefines short term as 10 years to better align with conservation planning. These changes are reflected in the IUCN Green Status of Species Standard.

Geological and hydrogeological assessment of the Brito Formation: Municipio de Tola, Nicaragua - James K. Adamson; G. Thomas LaVanchy; Brandon Stone; James A. Clark; Stuart J. Dykstra; Matthew J. Taylor (Hydrogeology Journal, 2021)
There are sparse hydrogeological data and insufficient hydrogeological knowledge in many areas of the world reliant on groundwater. Nicaragua’s Pacific coast is one such region that is also experiencing water scarcity resulting from increasing demand on groundwater resources and climate change. The primary source of water in the region is the aquifer system associated with the Brito Formation, which is a marine sedimentary stratum of mostly sandstone that blankets 75 km of coastline in southwest Nicaragua. This study focused on the Tola municipality with the objective to advance a conceptual understanding of the hydrogeology and to support sustainable water development. Results demonstrate a heterogeneous aquifer system with regional flow characteristics and other factors that influence groundwater availability and water quality. Primary porosity is low, and secondary porosity is the primary mechanism of aquifer storage and is influenced by geological structure and diagenesis processes. Groundwater recharge is spatially and temporally heterogeneous and direct recharge is low. Infiltration of streamflow and runoff, especially early in the rainy season, is thought to be a large component of groundwater recharge. Climate, flow and recharge dynamics, and low storage capacity make the Brito Formation a sensitive resource and vulnerable to drought, increased abstraction, and climate change. This assessment provides data and insights useful for informing future studies and investments within the region and may be applicable in other Central American and Caribbean nations with coastal sandstone aquifers.

Correction to: TCA cycle metabolic compromise due to an aberrant S‑nitrosoproteome in HIV‑associated neurocognitive disorder with methamphetamine use - Paschalis‑Thomas Doulias; Tomohiro Nakamura; Henry Scott; Scott R. McKercher; Abdullah Sultan; Amanda Deal; Matthew Albertolle; Harry Ischiropoulos; Stuart A. Lipton (Journal of NeuroVirology, 2021)

TCA cycle metabolic compromise due to an aberrant S-nitrosoproteome in HIV-associated neurocognitive disorder with methamphetamine use - Paschalis-Thomas Doulias; Tomohiro Nakamura; Henry Scott; Scott R. McKercher; Abdullah Sultan; Amanda Deal; Matthew Albertolle; Harry Ischiropoulos; Stuart A. Lipton (Journal of NeuroVirology, 2021)

Genetic analysis of endometriosis and depression identifies shared loci and implicates causal links with gastric mucosa abnormality - Emmanuel O. Adewuyi; Divya Mehta; Yadav Sapkota; Yadav Sapkota; Kosuke Yoshihara; Mette Nyegaard; Valgerdur Steinthorsdottir; Andrew P. Morris; Amelie Fassbender; Nilufer Rahmioglu; Immaculata De Vivo; Julie E. Buring; et al. (Human Genetics, 2021)

Transcriptional Profiling of Individual Airway Projecting Vagal Sensory Neurons - Stuart B. Mazzone; Luyi Tian; Aung Aung Kywe Moe; Matthew W. Trewella; Matthew E. Ritchie; Alice E. McGovern (Molecular Neurobiology, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Assessment of the technological variability in decorated Lapita pottery from Teouma, Vanuatu, by petrography and LA-ICP-MS: implications for Lapita social organisation - Mathieu Leclerc; Elle Grono; Stuart Bedford; Matthew Spriggs (Archaeological and Anthropological Sciences, 2019)

Upregulation of Proteolytic Pathways and Altered Protein Biosynthesis Underlie Retinal Pathology in a Mouse Model of Alzheimer’s Disease - Mehdi Mirzaei; Kanishka Pushpitha; Liting Deng; Nitin Chitranshi; Veer Gupta; Rashi Rajput; Abu Bakr Mangani; Yogita Dheer; Angela Godinez; Matthew J. McKay; Karthik Kamath; Dana Pascovici; et al. (Molecular Neurobiology, 2019)

Spatial resilience of the Great Barrier Reef under cumulative disturbance impacts - Camille Mellin; Samuel Matthews; Kenneth R.N. Anthony; Stuart C. Brown; M. Julian Caley; Kerryn A. Johns; Kate Osborne; Marjetta Puotinen; Angus Thompson; Nicholas H. Wolff; Damien A. Fordham; M. Aaron MacNeil (Global Change Biology, 2019)
In the face of increasing cumulative effects from human and natural disturbances, sustaining coral reefs will require a deeper understanding of the drivers of coral resilience in space and time. Here we develop a high‐resolution, spatially explicit model of coral dynamics on Australia's Great Barrier Reef (GBR). Our model accounts for biological, ecological and environmental processes, as well as spatial variation in water quality and the cumulative effects of coral diseases, bleaching, outbreaks of crown‐of‐thorns starfish ( Acanthaster cf. solaris ), and tropical cyclones. Our projections reconstruct coral cover trajectories between 1996 and 2017 over a total reef area of 14,780 km 2 , predicting a mean annual coral loss of −0.67%/year mostly due to the impact of cyclones, followed by starfish outbreaks and coral bleaching. Coral growth rate was the highest for outer shelf coral communities characterized by digitate and tabulate Acropora spp. and exposed to low seasonal variations in salinity and sea surface temperature, and the lowest for inner‐shelf communities exposed to reduced water quality. We show that coral resilience (defined as the net effect of resistance and recovery following disturbance) was negatively related to the frequency of river plume conditions, and to reef accessibility to a lesser extent. Surprisingly, reef resilience was substantially lower within no‐take marine protected areas, however this difference was mostly driven by the effect of water quality. Our model provides a new validated, spatially explicit platform for identifying the reefs that face the greatest risk of biodiversity loss, and those that have the highest chances to persist under increasing disturbance regimes.

The Australian National Rabbit Database: 50 yr of population monitoring of an invasive species - Emilie Roy‐Dufresne; Miguel Lurgi; Stuart C. Brown; Konstans Wells; Brian Cooke; Greg Mutze; David Peacock; Phill Cassey; Dave Berman; Barry W. Brook; Susan Campbell; Tarnya Cox; et al. (Ecology, 2019)
With ongoing introductions into Australia since the 1700s, the European rabbit ( Oryctolagus cuniculus ) has become one of the most widely distributed and abundant vertebrate pests, adversely impacting Australia's biodiversity and agroeconomy. To understand the population and range dynamics of the species and its impacts better, occurrence and abundance data have been collected by researchers and citizens from sites covering a broad spectrum of climatic and environmental conditions in Australia. The lack of a common and accessible repository for these data has, however, limited their use in determining important spatiotemporal drivers of the structure and dynamics of the geographical range of rabbits in Australia. To meet this need, we created the Australian National Rabbit Database, which combines more than 50 yr of historical and contemporary survey data collected from throughout the range of the species in Australia. The survey data, obtained from a suite of complementary monitoring methods, were combined with high‐resolution weather, climate, and environmental information, and an assessment of data quality. The database provides records of rabbit occurrence (689,265 records) and abundance (51,241 records, >120 distinct sites) suitable for identifying the spatiotemporal drivers of the rabbit's distribution and for determining spatial patterns of variation in its key life‐history traits, including maximum rates of population growth. Because all data are georeferenced and date stamped, they can be coupled with information from other databases and spatial layers to explore the potential effects of rabbit occurrence and abundance on Australia's native wildlife and agricultural production. The Australian National Rabbit Database is an important tool for understanding and managing the European rabbit in its invasive range and its effects on native biodiversity and agricultural production. It also provides a valuable resource for addressing questions related to the biology, success, and impacts of invasive species more generally. No copyright or proprietary restrictions are associated with the use of this data set other than citation of this Data Paper.

Real-Time Monitoring with a Tablet App Improves Implementation of Treatments to Enhance Forest Structural Diversity - Colin T Maher; Emily Oja; Abigail Marshall; Matthew Cunningham; Lucas Townsend; Graham Worley-Hood; Luke Ruffner Robinson; Taylor Margot; Drew Lyons; Stuart Fety; Eryn E Schneider; Sean M A Jeronimo; et al. (Journal of Forestry, 2019)

Mapping of novel salt tolerance QTL in an Excalibur × Kukri doubled haploid wheat population - Muhammad A. Asif; Rhiannon K. Schilling; Joanne Tilbrook; Chris Brien; Kate Dowling; Huwaida Rabie; Laura Short; Christine Trittermann; Alexandre Garcia; Edward G. Barrett-Lennard; Bettina Berger; Diane E. Mather; et al. (Theoretical and Applied Genetics, 2018)
Key message Novel QTL for salinity tolerance traits have been detected using non-destructive and destructive phenotyping in bread wheat and were shown to be linked to improvements in yield in saline fields. Abstract Soil salinity is a major limitation to cereal production. Breeding new salt-tolerant cultivars has the potential to improve cereal crop yields. In this study, a doubled haploid bread wheat mapping population, derived from the bi-parental cross of Excalibur × Kukri, was grown in a glasshouse under control and salinity treatments and evaluated using high-throughput non-destructive imaging technology. Quantitative trait locus (QTL) analysis of this population detected multiple QTL under salt and control treatments. Of these, six QTL were detected in the salt treatment including one for maintenance of shoot growth under salinity ( QG (1 – 5) .asl - 7A ), one for leaf Na + exclusion ( QNa.asl - 7A ) and four for leaf K + accumulation ( QK.asl - 2B.1 , QK.asl - 2B.2 , QK.asl - 5A and QK:Na.asl - 6A ). The beneficial allele for QG (1 – 5) .asl - 7A (the maintenance of shoot growth under salinity) was present in six out of 44 mainly Australian bread and durum wheat cultivars. The effect of each QTL allele on grain yield was tested in a range of salinity concentrations at three field sites across 2 years. In six out of nine field trials with different levels of salinity stress, lines with alleles for Na + exclusion and/or K + maintenance at three QTL ( QNa.asl - 7A , QK.asl - 2B.2 and QK:Na.asl - 6A ) excluded more Na + or accumulated more K + compared to lines without these alleles. Importantly, the QK.asl - 2B.2 allele for higher K + accumulation was found to be associated with higher grain yield at all field sites. Several alleles at other QTL were associated with higher grain yields at selected field sites.

Multilocus phylogenetics in a widespread African anuran lineage (Brevicipitidae: Breviceps ) reveals patterns of diversity reflecting geoclimatic change - Stuart V. Nielsen; Savel R. Daniels; Werner Conradie; Matthew P. Heinicke; Brice P. Noonan (Journal of Biogeography, 2018)
Aim To investigate models assessing the influence of geomorphology and climatic shifts on species diversification in sub‐Saharan Africa by reconstructing the pattern and timing of phylogenetic relationships of rain frogs (Brevicipitidae: Breviceps ). Location Sub‐Saharan Africa, south of the Congo Basin. Methods Multilocus sequence data were generated for near complete species‐level sampling of the genus Breviceps . Phylogenetic relationships were inferred via Bayesian inference and maximum likelihood analyses on both concatenated and single‐gene datasets. Network analyses identified locus‐specific reticulate relationships among taxa. Bayesian methods were used to infer dates of divergence among Breviceps lineages, and niche modelling was used to identify possible adaptive divergence. Results Breviceps is monophyletic and comprised of two major, largely allopatric subclades. Diversity within each subclade is concentrated in two areas with contrasting geologic and climatic histories: the arid/semiarid winter rainfall zone in the south‐western ( SW ) Cape, and the semitropical East Coast that receives predominantly summer rainfall. Recognized species diversity in the SW Cape based on phenotypic variation is consistent with observed genetic patterns whereas the East Coast is shown to harbour unexpectedly high genetic diversity and up to seven putative, cryptic species. Niche models show significant overlap between closely related species. Main conclusions Dating analyses indicate that diversification of Breviceps occurred rapidly within the Miocene, with only a moderate decline over the Plio‐Pleistocene, suggesting that this process might be slowed but ongoing. Our findings suggest that a combination of two models, a landscape barrier model and climate fluctuation model, can explain patterns of diversification in Breviceps . This demonstrates that Miocene epeirogenic events and climatic shifts may have had a considerable influence on contemporary patterns of biodiversity. Topographic complexity and relative geoclimatic stability in the East have promoted cryptic diversification in allopatry, and this area clearly harbours numerous undescribed taxa and is in need of detailed biotic investigation.

Effects of long-term dietary administration of estrogen receptor-beta agonist diarylpropionitrile on ovariectomized female ICR (CD-1) mice - Sherry A. Said; Rachel Isedowo; Christilynn Guerin; Navreek N. Nar; Leesa Lillie; Shawn Bukovac; Jonathan J. Simone; Matthew R. Green; Cheryl M. McCormick; Jeffrey A. Stuart (GeroScience, 2018)

Taxonomy of the family Arenaviridae and the order Bunyavirales: update 2018 - Piet Maes; Sergey V. Alkhovsky; Yīmíng Bào; Martin Beer; Monica Birkhead; Thomas Briese; Michael J. Buchmeier; Charles H. Calisher; Rémi N. Charrel; Il Ryong Choi; Christopher S. Clegg; Juan Carlos de la Torre; et al. (Archives of Virology, 2018)

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

Fish‐Net: Probabilistic models for fishway planning, design and monitoring to support environmentally sustainable hydropower - Martin Wilkes; Lee Baumgartner; Craig Boys; Luiz G M Silva; Justin O'Connor; Matthew Jones; Ivor Stuart; Evelyn Habit; Oscar Link; J Angus Webb (Fish and Fisheries, 2018)
The construction of fishways for upstream and downstream connectivity is the preferred mitigation measure for hydropower dams and other riverine barriers. Yet empirical evidence for effective design criteria for many species is missing. We therefore assembled a group of international fishway designers and combined their knowledge with available empirical data using a formal expert elicitation protocol and Bayesian networks. The expert elicitation method we use minimizes biases typically associated with such approaches. Demonstrating our application with a case‐study on the temperate Southern Hemisphere, we use the resulting probabilistic models to predict the following, given alternative design parameters: (i) the effectiveness of technical fishways for upstream movement of migratory fish; (ii) habitat quality in nature‐like bypasses for resident fish; and (iii) rates of mortality during downstream passage of all fish through turbines and spillways. The Fish Passage Network (Fish‐Net) predicts that fishways for native species could be near 0% or near 100% efficient depending on their design, suggesting great scope for adequate mitigation. Sensitivity analyses revealed the most important parameters as follows: (i) design of attraction and entrance features of technical fishways for upstream migration; (ii) habitat preferences of resident fish in nature‐like bypasses; and (iii) susceptibility of fish to barotrauma and blade strike during turbine passage. Numerical modelling predicted that mortality rates of small‐bodied fish (50–100 mm TL ) due to blade strike may be higher for Kaplan than Francis turbines. Our findings can be used to support environmentally sustainable decisions in the planning, design and monitoring stages of hydropower development.

Liposomal Amphotericin B as Monotherapy in Relapsed Coccidioidal Meningitis - Ethan R. Stewart; Matthew L. Eldridge; Ian McHardy; Stuart H. Cohen; George R. Thompson (Mycopathologia, 2018)

Soil carbon cycling proxies: Understanding their critical role in predicting climate change feedbacks - Vanessa L. Bailey; Ben Bond‐Lamberty; Kristen DeAngelis; A. Stuart Grandy; Christine V. Hawkes; Kate Heckman; Kate Lajtha; Richard P. Phillips; Benjamin N. Sulman; Katherine E. O. Todd‐Brown; Matthew D. Wallenstein (Global Change Biology, 2018)
The complexity of processes and interactions that drive soil C dynamics necessitate the use of proxy variables to represent soil characteristics that cannot be directly measured (correlative proxies), or that aggregate information about multiple soil characteristics into one variable (integrative proxies). These proxies have proven useful for understanding the soil C cycle, which is highly variable in both space and time, and are now being used to make predictions of the fate and persistence of C under future climate scenarios. However, the C pools and processes that proxies represent must be thoughtfully considered in order to minimize uncertainties in empirical understanding. This is necessary to capture the full value of a proxy in model parameters and in model outcomes. Here, we provide specific examples of proxy variables that could improve decision‐making, and modeling skill, while also encouraging continued work on their mechanistic underpinnings. We explore the use of three common soil proxies used to study soil C cycling: metabolic quotient, clay content, and physical fractionation. We also consider how emerging data types, such as genome‐sequence data, can serve as proxies for microbial community activities. By examining some broad assumptions in soil C cycling with the proxies already in use, we can develop new hypotheses and specify criteria for new and needed proxies.

The value of virtual conferencing for ecology and conservation - Hannah Fraser; Kylie Soanes; Stuart A. Jones; Chris S. Jones; Matthew Malishev (Conservation Biology, 2017)
The objectives of conservation science and dissemination of its research create a paradox: Conservation is about preserving the environment, yet scientists spread this message at conferences with heavy carbon footprints. Ecology and conservation science depend on global knowledge exchange—getting the best science to the places it is most needed. However, conference attendance from developed countries typically outweighs that from developing countries that are biodiversity and conservation hotspots. If any branch of science should be trying to maximize participation while minimizing carbon emissions, it is conservation. Virtual conferencing is common in other disciplines, such as education and humanities, but it is surprisingly underused in ecology and conservation. Adopting virtual conferencing entails a number of challenges, including logistics and unified acceptance, which we argue can be overcome through planning and technology. We examined 4 conference models: a pure‐virtual model and 3 hybrid hub‐and‐node models, where hubs stream content to local nodes. These models collectively aim to mitigate the logistical and administrative challenges of global knowledge transfer. Embracing virtual conferencing addresses 2 essential prerequisites of modern conferences: lowering carbon emissions and increasing accessibility for remote, time‐ and resource‐poor researchers, particularly those from developing countries.

A global analysis of traits predicting species sensitivity to habitat fragmentation - Douglas A. Keinath; Daniel F. Doak; Karen E. Hodges; Laura R. Prugh; William Fagan; Cagan H. Sekercioglu; Stuart H. M. Buchart; Matthew Kauffman (Global Ecology and Biogeography, 2017)
Aim Elucidating patterns in species responses to habitat fragmentation is an important focus of ecology and conservation, but studies are often geographically restricted, taxonomically narrow or use indirect measures of species vulnerability. We investigated predictors of species presence after fragmentation using data from studies around the world that included all four terrestrial vertebrate classes, thus allowing direct inter‐taxonomic comparison. Location World‐wide. Methods We used generalized linear mixed‐effect models in an information theoretic framework to assess the factors that explained species presence in remnant habitat patches (3342 patches; 1559 species, mostly birds; and 65,695 records of patch‐specific presence–absence). We developed a novel metric of fragmentation sensitivity, defined as the maximum rate of change in probability of presence with changing patch size (‘Peak Change’), to distinguish between general rarity on the landscape and sensitivity to fragmentation per se. Results Size of remnant habitat patches was the most important driver of species presence. Across all classes, habitat specialists, carnivores and larger species had a lower probability of presence, and those effects were substantially modified by interactions. Sensitivity to fragmentation (measured by Peak Change) was influenced primarily by habitat type and specialization, but also by fecundity, life span and body mass. Reptiles were more sensitive than other classes. Grassland species had a lower probability of presence, though sample size was relatively small, but forest and shrubland species were more sensitive. Main conclusions Habitat relationships were more important than life‐history characteristics in predicting the effects of fragmentation. Habitat specialization increased sensitivity to fragmentation and interacted with class and habitat type; forest specialists and habitat‐specific reptiles were particularly sensitive to fragmentation. Our results suggest that when conservationists are faced with disturbances that could fragment habitat they should pay particular attention to specialists, particularly reptiles. Further, our results highlight that the probability of presence in fragmented landscapes and true sensitivity to fragmentation are predicted by different factors.

Genotypic variation in foundation species generates network structure that may drive community dynamics and evolution - Matthew K. Lau; Arthur R. Keith; Stuart R. Borrett; Stephen M. Shuster; Thomas G. Whitham (Ecology, 2016)
Although genetics in a single species is known to impact whole communities, little is known about how genetic variation influences species interaction networks in complex ecosystems. Here, we examine the interactions in a community of arthropod species on replicated genotypes (clones) of a foundation tree species, Populus angustifolia James (narrowleaf cottonwood), in a long‐term, common garden experiment using a bipartite “genotype–species” network perspective. We combine this empirical work with a simulation experiment designed to further investigate how variation among individual tree genotypes can impact network structure. Three findings emerged: (1) the empirical “genotype–species network” exhibited significant network structure with modularity being greater than the highly conservative null model; (2) as would be expected given a modular network structure, the empirical network displayed significant positive arthropod co‐occurrence patterns; and (3) furthermore, the simulations of “genotype–species” networks displayed variation in network structure, with modularity in particular clearly increasing, as genotypic variation increased. These results support the conclusion that genetic variation in a single species contributes to the structure of ecological interaction networks, which could influence ecological dynamics (e.g., assembly and stability) and evolution in a community context.

Gene dynamics of toll-like receptor 4 through a population bottleneck in an insular population of water voles (Arvicola amphibius) - Martha K. Gavan; Matthew K. Oliver; Alex Douglas; Stuart B. Piertney (Conservation Genetics, 2015)

Small Molecule Specific Run Acceptance, Specific Assay Operation, and Chromatographic Run Quality Assessment: Recommendation for Best Practices and Harmonization from the Global Bioanalysis Consortium Harmonization Teams - Eric J. Woolf; Stuart McDougall; Douglas M. Fast; Maristela Andraus; Matthew Barfield; Michael Blackburn; Ben Gordon; David Hoffman; Noriko Inoue; Gabriel Marcelin-Jimenez; Amy Flynn; Richard LeLacheur; et al. (The AAPS Journal, 2014)

Resilience to Stress and Disturbance, and Resistance to Bromus tectorum L. Invasion in Cold Desert Shrublands of Western North America - Jeanne C. Chambers; Bethany A. Bradley; Cynthia S. Brown; Carla D’Antonio; Matthew J. Germino; James B. Grace; Stuart P. Hardegree; Richard F. Miller; David A. Pyke (Ecosystems, 2014)

Virus nomenclature below the species level: a standardized nomenclature for filovirus strains and variants rescued from cDNA - Jens H. Kuhn; Yīmíng Bào; Sina Bavari; Stephan Becker; Steven Bradfute; Kristina Brauburger; J. Rodney Brister; Alexander A. Bukreyev; Yíngyún Caì; Kartik Chandran; Robert A. Davey; Olga Dolnik; et al. (Archives of Virology, 2013)

Virus nomenclature below the species level: a standardized nomenclature for laboratory animal-adapted strains and variants of viruses assigned to the family Filoviridae - Jens H. Kuhn; Yiming Bao; Sina Bavari; Stephan Becker; Steven Bradfute; J. Rodney Brister; Alexander A. Bukreyev; Yíngyún Caì; Kartik Chandran; Robert A. Davey; Olga Dolnik; John M. Dye; et al. (Archives of Virology, 2013)

Individual variation in dispersal associated with phenotype influences fine-scale genetic structure in weasels - Allan D. McDevitt; Matthew K. Oliver; Stuart B. Piertney; Paulina A. Szafrańska; Marek Konarzewski; Karol Zub (Conservation Genetics, 2013)

Observations and implications of damage from the magnitude Mw 6.3 Christchurch, New Zealand earthquake of 22 February 2011 - Sean Wilkinson; Damian Grant; Elizabeth Williams; Sara Paganoni; Stuart Fraser; David Boon; Anna Mason; Matthew Free (Bulletin of Earthquake Engineering, 2013)

The size of savannah Africa: a lion’s (Panthera leo) view - Jason Riggio; Andrew Jacobson; Luke Dollar; Hans Bauer; Matthew Becker; Amy Dickman; Paul Funston; Rosemary Groom; Philipp Henschel; Hans de Iongh; Laly Lichtenfeld; Stuart Pimm (Biodiversity and Conservation, 2013)

Climate change, fuel and fire behaviour in a eucalypt forest - Stuart Matthews; Andrew L. Sullivan; Penny Watson; Richard J. Williams (Global Change Biology, 2012)
A suite of models was used to examine the links between climate, fuels and fire behaviour in dry eucalypt forests in south‐eastern Australia. Predictions from a downscaled climate model were used to drive models of fuel amount, the moisture content of fuels and two models of forest fire behaviour at a location in western Sydney in New South Wales, Australia. We found that a warming and drying climate produced lower fine fuel amounts, but greater availability of this fuel to burn due to lower moisture contents. Changing fuel load had only a small effect on fuel moisture. A warmer, drier climate increased rate of spread, an important measure of fire behaviour. Reduced fuel loads ameliorated climate‐induced changes in fire behaviour for one model. Sensitivity analysis of the other fire model showed that changes in fuel amount induced changes in fire behaviour of a similar magnitude to that caused directly by sensitivity to climate. Projection of changes in fire risk requires modelling of changes in vegetation as well as changes in climate. Better understanding of climate change effects on vegetation structure is required.

Pharmacokinetic Evaluation of Intranasally Administered Vinyl Polymer-Coated Lorazepam Microparticles in Rabbits - Yanjun Zhao; Marc B. Brown; Rajeshree H. Khengar; Matthew J. Traynor; Pedro Barata; Stuart A. Jones (The AAPS Journal, 2012)

The anatomy of population change in a black grouse population 1992–2008 - Matthew Geary; Alan H. Fielding; Stuart J. Marsden (Oecologia, 2012)

Spatial and temporal variabilities of δ13C and δ15N within lower trophic levels of a large lake: implications for estimating trophic relationships of consumers - Matthew M. Guzzo; G. Douglas Haffner; Stuart Sorge; Scott A. Rush; Aaron T. Fisk (Hydrobiologia, 2011)

Inducible expression of TGFβ, Snail and Zeb1 recapitulates EMT in vitro and in vivo in a NSCLC model - Gretchen M. Argast; Joseph S. Krueger; Stuart Thomson; Isabela Sujka-Kwok; Krista Carey; Stacia Silva; Matthew O’Connor; Peter Mercado; Iain J. Mulford; G. David Young; Regina Sennello; Robert Wild; et al. (Clinical & Experimental Metastasis, 2011)

Herbivore metabolism and stoichiometry each constrain herbivory at different organizational scales across ecosystems - Helmut Hillebrand; Elizabeth T. Borer; Matthew E. S. Bracken; Bradley J. Cardinale; Just Cebrian; Elsa E. Cleland; James J. Elser; Daniel S. Gruner; W. Stanley Harpole; Jacqueline T. Ngai; Stuart Sandin; Eric W. Seabloom; et al. (Ecology Letters, 2009)
Plant‐herbivore interactions mediate the trophic structure of ecosystems. We use a comprehensive data set extracted from the literature to test the relative explanatory power of two contrasting bodies of ecological theory, the metabolic theory of ecology (MTE) and ecological stoichiometry (ES), for per‐capita and population‐level rates of herbivory across ecosystems. We found that ambient temperature and herbivore body size (MTE) as well as stoichiometric mismatch (ES) both constrained herbivory, but at different scales of biological organization. Herbivore body size, which varied over 11 orders of magnitude, was the primary factor explaining variation in per‐capita rates of herbivory. Stoichiometric mismatch explained more variation in population‐level herbivory rates and also in per‐capita rates when we examined data from within functionally similar trophic groups (e.g. zooplankton). Thus, predictions from metabolic and stoichiometric theories offer complementary explanations for patterns of herbivory that operate at different scales of biological organization.

Spatio‐temporal variation in the strength and mode of selection acting on major histocompatibility complex diversity in water vole ( Arvicola terrestris ) metapopulations - MATTHEW K. OLIVER; XAVIER LAMBIN; THOMAS CORNULIER; STUART B. PIERTNEY (Molecular Ecology, 2009)
Patterns of spatio‐temporal genetic variation at a class II major histocompatibility complex (MHC) locus and multiple microsatellite loci were analysed within and between three water vole metapopulations in Scotland, UK. Comparisons of MHC and microsatellite spatial genetic differentiation, based on standardised tests between two demographically asynchronous zones within a metapopulation, suggested that spatial MHC variation was affected by balancing selection, directional selection and random genetic drift, but that the relative effects of these microevolutionary forces vary temporally. At the metapopulation level, between‐year differentiation for MHC loci was significantly correlated with that of microsatellites, signifying that neutral factors such as migration and drift were primarily responsible for overall temporal genetic change at the metapopulation scale. Between metapopulations, patterns of genetic differentiation implied that, at large spatial scales, MHC variation was primarily affected by directional selection and drift. Levels of MHC heterozygosity in excess of Hardy–Weinberg expectations were consistent with overdominant balancing selection operating on MHC variation within metapopulations. However, this effect was not constant among all samples, indicating temporal variation in the strength of selection relative to other factors. The results highlight the benefit of contrasting variation at MHC with neutral markers to separate the effects of stochastic and deterministic microevolutionary forces, and add to a growing body of evidence showing that the mode and relative strength of selection acting on MHC diversity varies both spatially and temporally.

A cross‐system synthesis of consumer and nutrient resource control on producer biomass - Daniel S. Gruner; Jennifer E. Smith; Eric W. Seabloom; Stuart A. Sandin; Jacqueline T. Ngai; Helmut Hillebrand; W. Stanley Harpole; James J. Elser; Elsa E. Cleland; Matthew E. S. Bracken; Elizabeth T. Borer; Benjamin M. Bolker (Ecology Letters, 2008)
Nutrient availability and herbivory control the biomass of primary producer communities to varying degrees across ecosystems. Ecological theory, individual experiments in many different systems, and system‐specific quantitative reviews have suggested that (i) bottom–up control is pervasive but top–down control is more influential in aquatic habitats relative to terrestrial systems and (ii) bottom–up and top–down forces are interdependent, with statistical interactions that synergize or dampen relative influences on producer biomass. We used simple dynamic models to review ecological mechanisms that generate independent vs. interactive responses of community‐level biomass. We calibrated these mechanistic predictions with the metrics of factorial meta‐analysis and tested their prevalence across freshwater, marine and terrestrial ecosystems with a comprehensive meta‐analysis of 191 factorial manipulations of herbivores and nutrients. Our analysis showed that producer community biomass increased with fertilization across all systems, although increases were greatest in freshwater habitats. Herbivore removal generally increased producer biomass in both freshwater and marine systems, but effects were inconsistent on land. With the exception of marine temperate rocky reef systems that showed positive synergism of nutrient enrichment and herbivore removal, experimental studies showed limited support for statistical interactions between nutrient and herbivory treatments on producer biomass. Top–down control of herbivores, compensatory behaviour of multiple herbivore guilds, spatial and temporal heterogeneity of interactions, and herbivore‐mediated nutrient recycling may lower the probability of consistent interactive effects on producer biomass. Continuing studies should expand the temporal and spatial scales of experiments, particularly in understudied terrestrial systems; broaden factorial designs to manipulate independently multiple producer resources (e.g. nitrogen, phosphorus, light), multiple herbivore taxa or guilds (e.g. vertebrates and invertebrates) and multiple trophic levels; and – in addition to measuring producer biomass – assess the responses of species diversity, community composition and nutrient status.

MicroCT Analysis of Symphyseal Ontogeny in Archaeolemur - Matthew J. Ravosa; Stuart R. Stock; Elwyn L. Simons; Ravinder Kunwar (International Journal of Primatology, 2007)

Nocturnal foraging by great skuas Stercorarius skua: implications for conservation of storm-petrel populations - Stephen C. Votier; Jonathan E. Crane; Stuart Bearhop; Ana de León; Claire A. McSorley; Eduardo Mínguez; Ian P. Mitchell; Matthew Parsons; Richard A. Phillips; Robert W. Furness (Journal of Ornithology, 2006)

Oblique photogrammetry with visible and thermal images of active lava flows - Mike R. James; Stuart Robson; Harry Pinkerton; Matthew Ball (Bulletin of Volcanology, 2006)

Isolation and characterization of a MHC class II DRB locus in the European water vole (Arvicola terrestris) - Matthew K. Oliver; Stuart B. Piertney (Immunogenetics, 2006)

A Comparison of Predictive Methods in Extinction Risk Studies: Contrasts and Decision Trees - Matthew S. Sullivan; Martin J. Jones; David C. Lee; Stuart J. Marsden; Alan H. Fielding; Emily V. Young (Biodiversity and Conservation, 2006)

Extinction Risk: Predicting, Assessing, Prioritisingand Redressing - Matthew S. Sullivan; Stuart J. Marsden (Biodiversity and Conservation, 2006)

Evidence and Implications of Recent Climate Change in Northern Alaska and Other Arctic Regions - Larry D. Hinzman; Neil D. Bettez; W. Robert Bolton; F. Stuart Chapin; Mark B. Dyurgerov; Chris L. Fastie; Brad Griffith; Robert D. Hollister; Allen Hope; Henry P. Huntington; Anne M. Jensen; Gensuo J. Jia; et al. (Climatic Change, 2005)

Habitat heterogeneity and niche structure of trees in two tropical rain forests - Matthew D. Potts; Stuart J. Davies; William H. Bossert; S. Tan; M. N. Nur Supardi (Oecologia, 2004)